Defective efferocytosis of vascular cells in heart disease - Singh, Bandana; Li, Kathryn; Cui, Kui; Peng, Qianman; Cowan, Douglas B.; Wang, Da-Zhi; Chen, Kaifu; Chen, Hong (Frontiers in Cardiovascular Medicine, 2022)
The efficient phagocytic clearance of dying cells and apoptotic cells is one of the processes that is essential for the maintenance of physiologic tissue function and homeostasis, which is termed “efferocytosis”. Under normal conditions, “find me” and “eat me” signals are released by apoptotic cells to stimulate the engulfment and efferocytosis of apoptotic cells. In contrast, abnormal efferocytosis is related to chronic and non-resolving inflammatory diseases such as atherosclerosis. In the initial steps of atherosclerotic lesion development, monocyte-derived macrophages display efficient efferocytosis that restricts plaque progression; however, this capacity is reduced in more advanced lesions. Macrophage reprogramming as a result of the accumulation of apoptotic cells and augmented inflammation accounts for this diminishment of efferocytosis. Furthermore, defective efferocytosis plays an important role in necrotic core formation, which triggers plaque rupture and acute thrombotic cardiovascular events. Recent publications have focused on the essential role of macrophage efferocytosis in cardiac pathophysiology and have pointed toward new therapeutic strategies to modulate macrophage efferocytosis for cardiac tissue repair. In this review, we discuss the molecular and cellular mechanisms that regulate efferocytosis in vascular cells, including macrophages and other phagocytic cells and detail how efferocytosis-related molecules contribute to the maintenance of vascular hemostasis and how defective efferocytosis leads to the formation and progression of atherosclerotic plaques.